PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN TERHADAP HASIL BELAJAR SISWA - Laia, Efrem Efektif (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research is motivated by the very low student learning outcomes in citizenship education subjects. The reason for the low student learning outcomes is because teachers are only focused on applying conventional learning methods. To overcome these low student learning outcomes, it is necessary to apply an appropriate learning model, namely the Probing Prompting learning model. The purpose of carrying out this research is to determine the effect of the Probing Prompting learning model on student learning outcomes. This research uses a quantitative approach with a quasi-experimental method. The sample for this research was class VII-A with a total of 34 students and class VII-B with a total of 33 students. The instrument used is a learning outcomes test which is divided into two, namely the initial test and the final test and documentation. Based on the results of data processing that has been carried out and hypothesis test calculations, =5.4 and , =1.68. This shows that the value >, then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the Probing Prompting learning model on student learning outcomes. This is because in the learning strategy there are several suggestions, namely 1) subject teachers should apply the Probing Prompting learning model because it can improve student learning outcomes. 2) there is student involvement in learning activities in class. 3) students are able to think actively